The potential of Cambodia’s solar technology market to support farmer-led irrigation - Minh, Thai Thi; Buntong, B.; Pavelic, Paul; Hin, L.; Flor, R. J. (DLG-Verlag GmbH, 2024)
Traditional irrigation systems in Cambodia, such as reservoirs, as well as river and canal systems, have limitations, leading to the emergence of farmer-led irrigation management. Meanwhile, solar irrigation has gained attention as a solution. However, challenges exist in matching demand with supply, as the solar irrigation market structure in Cambodia is monopolistic and limited in product choices. This article highlights the need for evidence-based targeting, stronger market demand-supply linkages, innovative marketing strategies and financing solutions to enable the uptake of solar irrigation and expand its potential benefits to farmers.